Space, Body and Montage in the Hybrid Installation Work of William Kentridge. (March 2014) - Rutherford, Anne
This article explores the recent animated film installations and operatic stage direction of William Kentridge to conceptualise emerging trends in installation work, artists' cinema and hybrid forms of the moving image. Kentridge opens new horizons for the articulation of the moving image with architectural space, reimagining the nature of film. Through a study of Kentridge's installation, I Am Not Me, The Horse Is Not Mine', his staging of the Shostakovich opera, The Nose, and his installation work at documenta 13, the article explores how Kentridge mobilises the full potential of the material encounter with the filmic image in new forms of dynamic montage. Drawing on understandings of the tactile, sensory, kinaesthetic engagement with the image, the article examines how Kentridge incorporates the three-dimensional spatiality and materiality of an exhibition/architectural space into the filmic. Through this enquiry, the article considers the broader significance of Kentridge's work for reconceptualising cinematic experience.